Language and Typology of Dakwahist Islamic Fundamentalism : The Study of Arabic Loanwords in The Religious Book of Jamaah Tablig - Sukron Kamil (Insaniyat : Journal of Islam and Humanities, 2016)
The study on the extrinsic language and its relation with religious system is important to undertake as it has strong intrinsic language paradigm. This paper found that there is a gap in the language research in response to a socio-cultural challenge. This paper studies the use of language and Islamic fundamentalism system in the religious book of Jamaah Tablig. The result shows that there is a correlation between them. The Arabic loanwords used by Jamaah Tablig in their preaching activities indicate that their religious system is fundamentalist. This paper uses the hermeneutical approach to study this topic. Next, this paper suggests that this group use the contextual and socio-cultural elements of the Quran, and do not use solely literal approach to the study of Islam (the Quran and the Muhammad tradition/Sunnah).DOI: 10.15408/insaniyat.v1i1.4341